In-Transit Metastasis From Squamous Cell Carcinoma. Issue 11 (November 2016) - Ma, Joyce H.Y.; Wu, Albert; Veness, Michael; Estall, Vanessa; Hong, Angela; Borg, Martin; James, Craig; Ibbetson, Jan; Ooi, Colin; Weightman, Warren; McColl, Ian; Hamann, Ian; et al.
Abstract : BACKGROUND: In-transit metastasis from cutaneous squamous cell carcinoma (SCC) is an uncommon form of metastasis through lymphatics and occurs more commonly in immunosuppressed patients. OBJECTIVE: To identify cases of in-transit SCC and determine patient characteristics, tumor features, management, and prognosis. METHODS AND MATERIALS: A multicenter case series treated by Australian and New Zealand clinicians. RESULTS: In 31 patients, median age was 72 years (range 52–99) and 68% were immunocompetent. Tumors occurred on the head and neck in 94% of cases, with 71% of all tumors occurring on the scalp, forehead, or temple. The median time to presentation with in-transit SCC from treatment of the initial tumor was 5 months. Management included surgery (94%), radiotherapy (77%), chemotherapy (10%), and reduction of immunosuppression (3%). Median follow-up was 12 months. Overall survival at 3 and 5 years were 27% and 13%, respectively. CONCLUSION: In-transit metastases are described in 31 patients, of whom the majority was immunocompetent. The scalp, forehead, and temple were the most common sites. New clinical and histological diagnostic criteria are proposed. Prognosis was poor with 5-year survival of 13%. Recommended management is a combination of surgery and adjuvant radiotherapy. Reduction of any iatrogenic immunosuppression should be considered.